Penerimaan Konsumen terhadap Edible Coating sebagai Teknologi Pengawetan Buah - Agustina, Julia; Nugrahaini, Amelia Dwi; Humaidi, Taufiq Rahman (Jurnal Kridatama Sains dan Teknologi, 2025)
Edible coating is one of the postharvest handling technology innovations that functions to extend the shelf life of fruit and maintain its quality. This study aims to analyze the level of consumer acceptance of the use of aloe vera-based edible coating on fruit. The research method used is quantitative with a descriptive approach. Data were obtained from 140 respondents through an online questionnaire and analyzed using the Likert scale and descriptive statistical analysis. The results showed that 82.86% of respondents were aware of edible coating, defined as a thin layer applied to the surface of fruit to extend shelf life, maintain quality, and enhance the safety and appearance of fruit products during storage and distribution. Social media serves as the primary source of consumer information about edible coating. Adequate knowledge and information regarding the safety of edible coating materials influence consumer decisions to purchase fruit products with edible coating. Therefore, more intensive education is needed to increase consumer acceptance of this innovation